Correlation between multifunctional properties of lead free Iron doped BCT perovskite ceramics - Redhu, Preeti; Punia, Rajesh; Hooda, Ashima; Malik, B. P.; Sharma, Geeta; Sharma, Preeti (Ceramics International, 2020)
Present study investigates the effect of Fe doping on structural, microstructural, dielectric, ferroelectric, piezoelectric and magnetic properties of Barium calcium titanate (BCT) ceramics synthesized by solid state reaction route. The polycrystalline tetragonal structure of prepared ceramics was confirmed from XRD study. Analysis done using Rietveld refinement reveals reduction in lattice parameters as well as unit cell volume on substitution of Fe3+ ions in BCT lattice. Occurrence of four distinct Raman bands viz. 297 cm(-1) -302 cm(-1), 473 cm(-1)-475 cm(-1), 516 cm(-1) -524 cm(-1) and 729 cm(-1) -733 cm(-1) in Raman spectroscopic studies confirms the tetragonal phase of prepared ceramic compositions which are in accordance with XRD study. The Scanning Electron Microscopy analysis revealed polyhedral shaped grains whose average grain size decreased with increase in Fe content (x) in BCT ceramics. A diffused frequency independent phase transition was observed in temperature dependent dielectric measurements. Dielectric properties improved significantly, with shifting of transition temperature, T c close to room temperature with Fe doping. These studiessuggest applications of these ceramics in the development of environment friendly dielectric materials meeting X7R MLCCs specifications. The ferroelectric and piezoelectric properties of these ceramic compositions were found to decrease with increase in Fe concentration. Feeble room temperature ferromagnetism was observed for composition x = 0.020.
Keywords: BCT; dielectric response; Fe doping; ferroelectric properties; Lead free ceramics; Magnetic measurements

Role of charge compensation mechanism and defect dipoles on properties of Mn doped BCT ceramics - Redhu, Preeti; Sharma, Preeti; Hooda, Ashima; Singh, Anupinder; Sharma, Geeta; Punia, Rajesh (Ceramics International, 2021)
Single-phase Mn doped Barium Calcium Titanate (BCT) (Ba0.80Ca0.20Ti1-xMnxO3; x = 0.000, 0.005, 0.010, 0.015 and 0.020) lead free ceramics have been prepared by conventional solid-state reaction method. XRD studies and Rietveld refinement confirmed the existence of tetragonal phase (P4mm) for all prepared ceramic compositions. The average grain size increased up to x = 0.005 and thereafter it decreased with increase in Mn content in BCT compositions. Analysis of temperature-dependent dielectric study revealed phase transformation from tetragonal to cubic phase and defect dipole induced anomaly in paraelectric region of temperature-dependent dielectric constant ( epsilon'-T) curve. Degree of diffusiveness increased with Mn doping in BCT ceramics as confirmed by evaluating diffused phase transition (DPT) parameters (gamma and delta(c)) by Power Law fitting and width of diffused phase transition (D') obtained from derivative of epsilon'-T curve. Ferroelectric (P-E loops) study revealed that ceramic composition with x = 0.015 Mn content showed the highest remnant polarization (P-r) and maximum polarization (P-max) of 14.10 mu C/cm(2) and 24.20 mu C/cm(2) respectively. Enhancement in energy storage properties with applied electric fields have been observed at room temperature. Maximum energy storage density W-rec similar to 190.89 mJ/cm(3) with an efficiency of 48.63% has been obtained for x = 0.015. A large piezoelectric charge coefficient (d(33)) of 460 pC/N has been obtained for x = 0.020. The room temperature magnetic measurements shows feeble ferromagnetism for Mn doped samples. These studies suggest the application of these ceramics for multilayer ceramic capacitors, energy storage, and high power applications..
Keywords: Defect dipoles; Dielectric anomaly; Energy storage; Ferroelectric materials; ferromagnetic materials; Lead-free ceramics; Mn doped BCT; piezoelectric; Williamson-Hall (W-H)